Nepogodbena odškodninska odgovornost in umetna inteligenca - Miklič, Samo (Pravni letopis, 2021)
The established non-contractual liability regimes are deeply embedded both in European legal systems and worldwide. The continuity of product liability, strict and fault liability, and vicarious liability, as well as other established types of liability, shows their ability to cover every possible case of damage one can think of. Are these pillars of civil law effective, however, when a new injuring party - artificial inteligence - emerges? Legal scholars provide both affirmative and dissenting answers to this question. Some would only adapt the current framework of civil liability, others claim that new legal constructs need to be established. Despite their differences, however, most scholars agree, that in order to maximize the advantages of artificial inteligence, law needs to closely follow its evolution.
Keywords: civilno pravo; krivda; odgovornost; odškodninska odgovornost; odškodninsko pravo; osebna odgovornost; škoda; tehnološke inovacije; umetna inteligenca